The perceived effect of intellectual capital on the performance of a higher education institution: A case study - Gradim, A.; Neris, E.; Vale, J.; Matos, F. (Proceedings of the 23rd European Conference on Knowledge Management, ECKM 2022, 2022)
During an increasingly competitive environment, where digital technologies play a crucial role, organisations began to seek competitive advantages in their intangible resources to survive. Therefore, organisations’ intellectual capital (IC) is considered an essential source of competitive advantages. Higher Education Institutions (HEI) have also recognised the relevance of this phenomenon since these organisations use their IC to produce knowledge. In response to the call to analyse IC in practice, which includes emerging countries, this paper’s goal is twofold. On the one hand, it aims to assess the perceptions of a Brazilian HEI’s internal stakeholders regarding the relative importance of each IC dimension. On the other hand, it intends to understand how IC influences the performance of these organisations. Additionally, it intends to comprehend how internal stakeholders perceive and might measure performance. A case study was conducted at the Brazilian Federal Institute of Education, Science and Technology of Mato Grosso. The findings suggest that the three traditional IC dimensions are equally important to create competitive advantages, although there is no unanimity regarding which is the most important. They also show that IC influences, through several means, the performance of the HEI, although there was a focus on individual performance and also on negative issues, something which may, potentially, be caused by some lack of knowledge regarding the IC concept. Another finding is the lack of awareness regarding the importance of digital technologies in improving IC. Finally, an overlap between IC and performance indicators has been noticed. This study contributes to developing awareness about the relevance of intellectual capital in HEIs pertaining to emerging countries and its importance in improving their performance.